Analysis Risk Management of Procurement System Goods/Services (Study Case in PT. Perusahaan Listrik Negara (PERSERO) of East Java Distribution, South Surabaya Service Area and Network - Oryza Tannar (Journal of Economics, Business, and Government Challenges, 2019)
Procurement is expected to be carried out effectively and efficiently with the principles of fair competition, transparent ,opened and fair treatment for all parties, in accordance with Peraturan Presiden Nomor 54 Tahun 2010 on Government Procurement is an activity to obtain goods and services by the Ministry/Institutions/Regional Working Units/other Institutions starting from the planning process needs to be disclosed all activities to obtain goods and services. As the development of an increasingly modern era, the government infrastructure was varied to keep track of and adapted to the needs of the government. The procurement of goods and services financed by the budget of revenues and expenditures country / region. This study focuses on government procurement of goods and services made in the area of PT. Perusahaan Listrik Negara (PERSERO) of East Java Distribution, South Surabaya Service Area and Network (PT. PLN Disjatim) by using the historical approach, sociological approach, institutional approaches, legal and political approach to development based on risk management. The data in this study were obtained by physical or direct data approach with several parties and employees concerned with the procurement of goods and services within the state electricity distribution company of the Eastern Java. The results of this study include the procurement of goods and services in the state electricity company disjatim generally been in accordance with the systems and mechanisms that have been defined in the Peraturan Presiden 54 Tahun 2010 on Government Procurement. However, once studied and reviewed more deeply there are some constraints and the presence of fraudulent behavior committed by the procurement committee and procurement participants and parties involved in the procurement of goods and services.